2008
DOI: 10.1071/ea07131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormonal growth promotants (HGP) on growth, carcass characteristics, the palatability of different muscles in the beef carcass and their interaction with aging

Abstract: Abstract. Effects of hormonal growth promotant (HGP) implantation on liveweight, carcass and meat quality measurements were examined using 80 Angus yearling cattle. After entry to the feedlot, 40 steers and 40 heifers were implanted with Revalor-S (28 mg oestradiol and 140 mg trenbolone acetate) and Revalor-H (20 mg oestradiol, 200 mg trenbolone acetate), respectively. Cattle were slaughtered after 55 and 65 days on feed. Samples from the Mm. longissimus dorsi, biceps femoris (the cap and body portions), glute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 28 publications
3
21
0
2
Order By: Relevance
“…et al (1991) 0.12 0.20 Huck et al (1991) 0.23 0.20 Hunt et al (1991) -0.15 0.39 Gerken et al (1995) 0.40 0.25 Samber et al (1996) 0.24 0.10 Foutz et al (1997) 0.32 0.17 Rumsey et al (1999) 0.95 0.33 Pritchard et al (2000) 0.00 0.20 Roeber et al (2000) 0.37 0.11 Barham et al (2003) 0.37 0.11 Platter et al (2003) 0.63 0.19 Reiling & Johnson (2003) WA-1 trial: Thompson et al (2008a) This trial, utilising three cooking methods, covered a wide range of muscles for heifers and steers. The details are covered in full in Thompson et al (2008a). Here only the details for the M. longissimus for steers are extracted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…et al (1991) 0.12 0.20 Huck et al (1991) 0.23 0.20 Hunt et al (1991) -0.15 0.39 Gerken et al (1995) 0.40 0.25 Samber et al (1996) 0.24 0.10 Foutz et al (1997) 0.32 0.17 Rumsey et al (1999) 0.95 0.33 Pritchard et al (2000) 0.00 0.20 Roeber et al (2000) 0.37 0.11 Barham et al (2003) 0.37 0.11 Platter et al (2003) 0.63 0.19 Reiling & Johnson (2003) WA-1 trial: Thompson et al (2008a) This trial, utilising three cooking methods, covered a wide range of muscles for heifers and steers. The details are covered in full in Thompson et al (2008a). Here only the details for the M. longissimus for steers are extracted.…”
Section: Resultsmentioning
confidence: 99%
“…The studies considered in this meta-analysis are papers that have appeared in refereed journals for which estimates and standard errors are available, including the recent Australian studies (Hunter et al 2001;Thompson et al 2008aThompson et al , 2008bWatson et al 2008b;McIntyre et al unpubl. data) summarised in the Results section.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Thompson et al (2008) showed that the effects of HGP interact with muscle, being larger in muscles with the greatest ageing rate, such as the striploin, and also that the reductions in consumer panel scores (for steers implanted with Revalor-S and heifers implanted with Revalor-H) were greater for steaks aged for 7 d (the time at which our MSA consumer assessments are conducted) than those aged for 21 d.…”
Section: Discussionmentioning
confidence: 99%
“…The use of HGPs has been studied extensively in the database (Thompson et al 2008a;Watson 2008;Watson et al 2008b), and in a range of associated experiments reported elsewhere. The result was an HGP penalty of the order of 3-6 MQ points on meat palatability, depending on the muscle which is further adjusted with aging.…”
Section: Hgp Implantsmentioning
confidence: 99%